Mechanism and subpopulation specificity of mitochondrial reactive oxygen species release in the post-ischemic hyperthyroid myocardium - de Mooy, Anthony Brett, author; Chicco, Adam J., advisor; Frye, Melinda, advisor; Gentile, Christopher, committee member (Colorado State University. Libraries, 2012)
Hyperthyroidism (HT) augments release of reactive oxygen species (ROS) from cardiac mitochondria following myocardial ischemia/reperfusion (I/R). The present study examined the mechanisms of this phenomenon and determined whether subsarcolemmal (SSM) and intermyofibrillar mitochondria (IFM) are differentially affected. Male SD rats received 10 daily injections of thyroid hormone (30ug/kg i.p.; HT) or vehicle (CON) before hearts were excised and exposed to a 20/25 min global I/R protocol ex vivo. Following I/R, ROS release was assessed in freshly isolated SSM and IFM using the Amplex Red assay with a variety of substrate and inhibitor combinations to examine sites and mechanisms of release. ROS release from SSM exceeded IFM in CON and HT hearts by 25-50% following I/R (P < 0.01). Surprisingly, HT augmented ROS release from SSM, but decreased ROS release from IFM (P < 0.05 for both). Blocking electron flow from respiratory complex 1 to 3 abolished the effect of HT on SSM, but not IFM. Inhibition of uncoupling proteins with GDP abolished the HT-induced reduction in IFM, but had little effect in SSM. Maximally uncoupling mitochondria with FCCP abolished effects of HT in IFM and SSM. Collectively, results indicate that 1) complex 3 in SSM is the primary source of mitochondrial ROS release following I/R in HT, and 2) enhanced activity of uncoupling proteins limits ROS release from IFM under these conditions.
Keywords: subpopulations; hyperthyroidism; ischemia; mitochondria; ROS